Anthocyanin-Rich Extract Mitigates the Contribution of the Pathobiont Genus Haemophilus in Mild-to-Moderate Ulcerative Colitis Patients - Yannik Zobrist; Michael Doulberis; Luc Biedermann; Gabriel E. Leventhal; Gerhard Rogler (Microorganisms)
Anthocyanins (ACs) have been shown to elicit anti-inflammatory and antioxidant effects in animal models of ulcerative colitis (UC). Furthermore, we previously observed in a double-blind randomized trial in UC patients that biochemical disease activity tended to be lower in patients that were exposed to AC. Here, we report on the changes in the fecal microbiome composition in these patients upon AC exposure. UC patients received a 3 g daily dose of an AC-rich bilberry extract (ACRE) for eight weeks. We determined the microbiome composition in longitudinal stool samples from 24 patients and quantified the degree of change over time. We also correlated the relative abundances of individual microbial taxa at different timepoints to fecal concentrations of calprotectin, a proxy for inflammation. Microbiome composition did not change over time as a result of the intervention, in terms of both alpha and beta diversity. However, before the intervention, the abundance of Haemophilus parainfluenzae was positively correlated with fecal calprotectin concentrations, and this correlation persisted in placebo-treated subjects throughout the study. In contrast, the correlation between H. parainfluenzae and calprotectin vanished in ACRE-treated subjects, while the relative abundance of H. parainfluenzae did not change. Our results suggest that ACRE treatment mitigates the contribution of H. parainfluenzae to inflammation. Further research is warranted to better comprehend the role of microbial composition in response to medical therapy including AC-rich extract in UC patients.